Self-Acceptance in Black and White - Abigail Hasberry (MDPI AG, 2019)
This reflective, autoethnographic qualitative case study at focus in this article is based on broader research on the experiences of Black teachers working at predominantly white and affluent private schools in the United States. It was motivated by the author/researcher’s own experiences of personal, academic, and professional racial identity development as a student, educator, parent, and educational administrator while living and working in predominantly white and affluent communities. The two main research questions this study engaged were: (1) How did the author/researcher develop her Black identity as a transracial adoptee living at the intersection of race and class; and, (2) What was the author/researcher’s journey towards her present state of racial self-acceptance and understanding? Three ancillary research questions were also engaged: (a) How did social and societal factors influence the author/researcher’s racial identity development? (b) How did the author/researcher build a support network of personal and professional community? and, (c) How was the author/researcher able to get to a place of self-love? Using Hill Collins’ (1998) intersectional analysis framework and Cross’s (1991) theory of Black racial identity development, this article explores the author/researcher’s experiences as an affluent racialized minority by unpacking lived experiences, coping strategies, and support mechanisms that led to her current professional calling.